Environmental and sociocultural issues: the movie "Brave New Land” (Brava Gente Brasileira) and dialogues with students in the Institutional Scholarship Program for Teaching Initiation (PIBID – Biology) - Pereira, Danielle Cristina; Gonçalves, Laise Vieira; Nascimento Junior, Antonio Fernandes (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This work was carried out based on an analysis of the assessment made by students in the Institutional Scholarship Program for Teaching Initiation in Biological Sciences (PIBID) at the Universidade Federal de Lavras - MG (UFLA), where they presented their insights about the movie “Brave New Land” (Brava Gente Brasileira). The objective was to seek elements that demonstrate how the film dialogues with sociocultural and environmental issues, promoting addition to the training of biology teachers. With this goal, we used qualitative research that fits the content analysis, categorizing these students’ common statements. We found 5 categories exposed in a frame, where we noticed how sociocultural issues stand out, however, the film brings relevant considerations about the Pantanal environment and the relationship between the traditional peoples with this place. Thus, it is possible to conclude that cinematographic art manages to dialogue and build a critical view of the relationships of the most diverse cultures with the collective and the environment.